Factors Related to Acceptance of Covid-19 Vaccine among Hemodialysis Patients in Indonesia: Factors Related to Acceptance of Covid-19 Vaccine among Hemodialysis Patients - Langgeng Perdhana; Suryani Yuliyanti; Shofa Chasani; Muchlis Achsan Udji Sofro (Journal of Tropical Life Science, 2022)
Hemodialysis patients are at risk of being infected with Corona Virus Disease 2019 (Covid-19). On the other hand. End-Stage Kidney Disease (ESKD) plays a role as a predictor factor of severe Covid-19 infection. There is no data about factors that affect Covid-19 vaccine acceptance among hemodialysis patients in Indonesia. This studyâ€™s goal is to determine the factors related to Covid-19 vaccine acceptance among hemodialysis patients. A Cross-sectional study occurred in September 2021 in the hemodialysis unit at Roemani Muhammadiyah Hospital Semarang. Inclusion criteria include ESKD patients who underwent hemodialysis â‰¥3 months, hemodialysis frequency twice a week, communicable, and agree to join in this study. While patients with incomplete data. and being treated in the Covid-19 isolation ward are excluded from this study. Collected data analyzed using chi-square using Statistical Program for Social Science (SPSS) 18.0 version. From 87 respondents, 36 (41.4%) respondents have been vaccinated and 51 (58.6%) respondents have not been vaccinated. Hemodialysis patients with high educational level, elderly, and has undergone hemodialysis >18 months have higher acceptances of Covid-19 vaccine (57.1% and 33.9%; 60.9% and 34.4%; 51% and 38.5%, p-value 0.04; 0.027; 0.03. Prevalence Ratio (PR) = 1.7; 1.8; 1.8). While gender, marital status, and history of Covid-19 infection did not have a significant relationship to Covid-19 vaccine acceptance (p > 0.05). Educational level, elderly patients, and duration of hemodialysis have a higher acceptance of the Covid-19 vaccine among the hemodialysis population.